European Union Financial Crisis: A Marxist Analysis - Farneubun, Petrus K (Universitas Muhammadiyah Yogyakarta, 2016)
European financial crisis poses a serious challenge to the fundamental structure of the European Union, political and financial institutions, as well as the values that bind European together. Different factors have been suggested as the causes of the crisis notably the failure of national government and economic policies. Responding to the crisis, numerous attemps have been proposed to accelerate the recovery, but the crisis still hit Eurozone and brought serious consequences politically and economically. In one side, the crisis severely damages some EU member economy but on the other side, the crisis advantages the other members. Such an inequality not only leads to the crisis but also exacerbate the crisis. Having said that, this paper will demonstrate that marxian conceptual model of inequality or constructed economic imbalance provides a better explanation regarding the causes ofthe crisis. Using marxist theoretical framework, this article will further show that introduction of Euro, the accumulation of profit and capital as well as the current European financial system built upon the spirit of capitalism and neoliberalism as the key factors contributing to the crisis and creating inequality.